Penolakan Pembangunan Rumah Ibadah Di Parit Mayor Kubu Raya Kalimantan Barat - Trio Saputra; Muhammad Kodri; Ahmad Jais (AL-Ikhtiar : Jurnal Studi Islam, 2025)
Rejection of the construction of houses of worship is a form of socio-religious conflict that still frequently arises in Indonesia's multicultural society. Although freedom of religion and worship is constitutionally guaranteed, local realities show that the establishment of houses of worship often faces various obstacles, both social and administrative. The case of the rejection of the construction of a house of worship in Parit Mayor, Kubu Raya Regency, is a concrete example of how religious issues can develop into social conflict if not managed wisely and participatory. This paper aims to analyze the factors underlying this rejection, while also examining the dynamics of the conflict and strategies for resolving it. This research uses a descriptive qualitative approach through literature review and analysis of relevant documents, grounded in theories of conflict resolution and interfaith harmony. This approach allows the author to understand the conflict comprehensively, not only from a legal perspective, but also from the social and cultural dimensions of the local community. The study results indicate that the rejection of the construction of houses of worship in Parit Mayor is influenced by several main factors, including the heterogeneous socio-cultural conditions of the community, prejudice and distrust between religious communities, differences in interpretation of regulations regarding the construction of houses of worship, and weak communication and public participation in the licensing process. The conflict, which was initially administrative in nature, then developed into a socio-religious conflict due to the lack of space for dialogue and transparency. Therefore, the local government has a strategic role in resolving the conflict through a participatory mediation approach, strengthening interfaith dialogue, enforcing fair and consistent laws, and integrating conflict resolution into regional development policies. This comprehensive approach is important to maintain interfaith harmony and prevent the recurrence of similar conflicts in the future. Abstrak Penolakan pembangunan rumah ibadah merupakan salah satu bentuk konflik sosial-keagamaan yang masih kerap muncul di tengah masyarakat multikultural Indonesia. Meskipun kebebasan beragama dan beribadah telah dijamin secara konstitusional, realitas di tingkat lokal menunjukkan bahwa pendirian rumah ibadah sering menghadapi berbagai hambatan, baik bersifat sosial maupun administratif. Kasus penolakan pembangunan rumah ibadah di Parit Mayor, Kabupaten Kubu Raya, menjadi contoh konkret bagaimana persoalan keagamaan dapat berkembang menjadi konflik sosial apabila tidak dikelola secara bijak dan partisipatif. Tulisan ini bertujuan untuk menganalisis faktor-faktor yang melatarbelakangi penolakan tersebut, sekaligus mengkaji dinamika konflik yang terjadi serta strategi penyelesaiannya. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui metode studi pustaka dan analisis dokumen yang relevan, dengan landasan teori resolusi konflik dan kerukunan umat beragama. Pendekatan ini memungkinkan penulis untuk memahami konflik secara komprehensif, tidak hanya dari aspek hukum, tetapi juga dari dimensi sosial dan kultural masyarakat setempat. Hasil kajian menunjukkan bahwa penolakan pembangunan rumah ibadah di Parit Mayor dipengaruhi oleh beberapa faktor utama, antara lain kondisi sosial-kultural masyarakat yang heterogen, adanya prasangka dan ketidakpercayaan antarumat beragama, perbedaan tafsir terhadap regulasi pendirian rumah ibadah, serta lemahnya komunikasi dan partisipasi publik dalam proses perizinan. Konflik yang pada awalnya bersifat administratif kemudian berkembang menjadi konflik sosial-keagamaan akibat minimnya ruang dialog dan transparansi. Oleh karena itu, pemerintah daerah memiliki peran strategis dalam menyelesaikan konflik melalui pendekatan mediasi partisipatif, penguatan dialog lintas agama, penegasan hukum yang adil dan konsisten, serta integrasi resolusi konflik ke dalam kebijakan pembangunan daerah. Pendekatan yang komprehensif ini penting untuk menjaga kerukunan umat beragama dan mencegah terulangnya konflik serupa di masa mendatang.